1995
DOI: 10.1111/j.1365-2095.1995.tb00033.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood chemistry and organ nutrient composition in Atlantic salmon, Salmo salar L., fed graded amounts of wheat starch

Abstract: After feeding Atlantic salmon, Salrno salar L., five graded amounts of wheat starch from 0 to 310 g kg-', low but increased levels of glycogen in kidney, heart and gills were determined. No variations were found in proximate or glycogen compositions of muscle, whereas the liver composition reflected the diet composition. Whole-body homogenates varied in dry matter and lipid levels; the variation was according to g lipid eaten per fish. Plasma glucose levels ranged above average levels only when the starch leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
67
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(91 citation statements)
references
References 20 publications
21
67
0
3
Order By: Relevance
“…Hemre et al (1995) reported that feeding of G wheat in the diet of salmon increased plasma glucose level, which is in agreement with the findings of the present study. Gelatinization of the starch results in hydratatization and shortening of the starch chain, which improves its digestibility and therefore increased glucose concentration in the blood.…”
Section: Discussionsupporting
confidence: 96%
“…Hemre et al (1995) reported that feeding of G wheat in the diet of salmon increased plasma glucose level, which is in agreement with the findings of the present study. Gelatinization of the starch results in hydratatization and shortening of the starch chain, which improves its digestibility and therefore increased glucose concentration in the blood.…”
Section: Discussionsupporting
confidence: 96%
“…In the present study, the serum total protein content was significantly lower in the 53% CHO group than that in the control group at 12 h. It indicated that the excess dietary CHO have an immuno-suppressive effect on Wuchang bream. The results were in agreement with the previous study in fish in which the serum total protein content was negatively correlated with dietary carbohydrate (Hemre et al, 1995). Serum aspartate aminotransferase, ubiquitous aminotransferase located in the mitochondria of fish, is an important index for the diagnosis of liver function and damage (Cho et al, 1994;Liu et al, 2010).…”
Section: Resultssupporting
confidence: 82%
“…The presence of undigested carbohydrate in the gut environment [26] may represent a selective media for the growth of different bacterial species [27], thus inducing bacterial metabolism and virulence mechanisms.…”
Section: Introductionmentioning
confidence: 99%